THE COMMUNITY OF INQUIRY FRAMEWORK IN ONLINE ENGLISH LEARNING: INSIGHTS FROM INDONESIAN CULTURAL CONTEXTS - Rasikawati, Ira; Yuyun, Ignasia; Wicks, David (LLT Journal: A Journal on Language and Language Teaching, 2024)
This research is grounded in the theoretical foundation of the Community of Inquiry (CoI) Framework, exploring its application within the context of Indonesian cultural values in English education. The objective of this case study is to examine how English instructors adapt their teaching strategies to the challenges of online learning. The research design employs a qualitative approach, centered on interviews with three instructors from an English department at a private university in Jakarta. The participants, representing a small but focused population, were selected through a reputational purposive sampling technique, based on nominations from students who identified them for their effectiveness and expertise in online English learning. Data collection involved in-depth interviews, providing insights into the instructors’ perspectives and experiences. The analysis involved a thematic examination of teaching, cognitive, and social presence in the CoI framework. Findings show a robust teaching presence and a significant cognitive presence. Notably, social presence, crucial to CoI, subtly aligns with Indonesian hierarchical culture. This study underlines the complex relationship between CoI and cultural factors in online education. It suggests incorporating pedagogies aligned with local cultural values to improve engagement and outcomes in Indonesian online English learning.